Assessment the Nurses’ Knowledge about Family Planning Methods in Health Centers in Lattakia - Mostafa, Nisreen; Saleh, Linda; Al-Shawakh, Manal (Latakia University Journal -Medical Sciences Series, 2020)
This study aimed to assessing the knowledge of Nurses about family planning methods in Health Centers in Lattakia, Data collected from 1/12 /2018 to 1/2/2019. The sample comprised of 29 nurses whose working in Health centers – Reproductive Health Clinics. Tool in two parts was been used. This study found that more than half of the nurses had average level of knowledge about family planning methods, the Knowledge about family planning methods weren’t statically associated with nurses’ demographics data. So it was recommended to prepare training program about family planning methods for nurses, supply the nurses with guides on family planning methods, and health centers with posters on family planning methods. أجريت هذه الدراسة بهدف تقييم معلومات الممرضات عن وسائل تنظيم الأسرة في المراكز الصحية في مدينة اللاذقية في الفترة الواقعة بين 1/12/2018 وحتى 1/2/2019. وشملت الدراسة الحالية (29) ممرضة تعمل في المراكز الصحية- عيادات الصحة الإنجابية. تم استخدام أداة من جزأين، تم الطلب إلى جميع الممرضات المشاركات في الدراسة الإجابة على أداة الدراسة. وكانت أهم النتائج التي توصلت الدراسة إليها أنّ أكثر من نصف الممرضات لديهن معلومات متوسطة عن وسائل تنظيم الأسرة، ولا علاقة للمواصفات الديموغرافية للممرضات بمستوى معلوماتهن عن وسائل تنظيم الأسرة، لذا يُقترح إجراء برامج تدريبية للممرضات عن وسائل تنظيم الأسرة وخاصة الحديثة منها، توزيع دليل ووضع ملصقات عن وسائل تنظيم الأسرة في المراكز الصحية.